Multipotent mesenchymal stem cells in lung fibrosis - Hostettler, Katrin E. (PLoS One, 2017)
RATIONALE: Stem cells have been identified in the human lung; however, their role in lung disease is not clear. We aimed to isolate mesenchymal stem cells (MSC) from human lung tissue and to study their in vitro properties. METHODS: MSC were cultured from lung tissue obtained from patients with fibrotic lung diseases (n = 17), from emphysema (n = 12), and normal lungs (n = 3). Immunofluorescence stainings were used to characterize MSC. The effect of MSC-conditioned media (MSC-CM) on fibroblast proliferation and on lung epithelial wound repair was studied. RESULTS: Expression of CD44, CD90, and CD105 characterized the cells as MSC. Moreover, the cells stained positive for the pluripotency markers Oct3/4 and Nanog. Positive co-stainings of chemokine receptor type 4 (CXCR4) with CD44, CD90 or CD105 indicated the cells are of bone marrow origin. MSC-CM significantly inhibited the proliferation of lung fibroblasts by 29% (p = 0.0001). Lung epithelial repair was markedly increased in the presence of MSC-CM (+ 32%). Significantly more MSC were obtained from fibrotic lungs than from emphysema or control lungs. CONCLUSIONS: Our study demonstrates enhanced numbers of MSC in fibrotic lung tissue as compared to emphysema and normal lung. The cells inhibit the proliferation of fibroblasts and enhance epithelial repair in vitro. Further in vivo studies are needed to elucidate their potential role in the treatment of lung fibrosis.